2017
DOI: 10.18632/oncotarget.22227
|View full text |Cite
|
Sign up to set email alerts
|

Serum corin is associated with the risk of chronic heart failure

Abstract: It has been well documented that corin is a critical protease involved in the regulation of blood pressure and cardiac function. We performed a case-control study to determine whether serum corin is associated with the risk of chronic heart failure (CHF). We included 484 consecutive CHF patients and 484 control subjects to investigate the potential relationship between serum corin and CHF using logistic regression analysis. Compared with healthy controls, the CHF patients were more likely to have histories of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Additionally, corin is also found in the blood system in its circulating forms. Previous studies demonstrated the decreased concentration of soluble circulating corin in patients with HF and acute myocardial infarction, compared to healthy individuals (183)(184)(185)(186)(187)(188)(189)(190)(191). Noteworthy, clinical studies demonstrated that decompensated heart failure, assessed by edema and elevated plasma ANP/BNP levels, is associated with reduced corin levels and decreased cleavage of proANP/proBNP peptides (179,(192)(193)(194)(195).…”
Section: Natriuretic Peptides Blunted Response In Heart Failurementioning
confidence: 99%
“…Additionally, corin is also found in the blood system in its circulating forms. Previous studies demonstrated the decreased concentration of soluble circulating corin in patients with HF and acute myocardial infarction, compared to healthy individuals (183)(184)(185)(186)(187)(188)(189)(190)(191). Noteworthy, clinical studies demonstrated that decompensated heart failure, assessed by edema and elevated plasma ANP/BNP levels, is associated with reduced corin levels and decreased cleavage of proANP/proBNP peptides (179,(192)(193)(194)(195).…”
Section: Natriuretic Peptides Blunted Response In Heart Failurementioning
confidence: 99%
“…[16][17][18] Clinical and translational studies conducted over the past decade strongly support the pro-ANP convertase CORIN as a biomarker and effector of HF and myocardial infarction. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] CORIN is proteolytically cleaved from the cell membrane and released into circulation as soluble fragments of different sizes. Heart failure and acute myocardial infarction affect cardiac corin expression and shedding by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…24,30,31 Plasma and cardiac CORIN levels decreased in patients with HF and animal models of HF. 14,16,21,24,29,32 So far, several newly published randomized controlled trials have compared the evaluation of CORIN between heart failure group and control group. In order to fully evaluate the role of CORIN, relevant articles are included to evaluate CORIN levels from a different direction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations